(untitled) (Journal Of Educational and Psychological Researches, 2022)
The current study aimed to identify the difficulties faced by the student in mathematics and possible proposals to address these difficulties. The study used a descriptive method also used the questionnaire to collect data and information were applied to a sample of (163) male and female teachers. The results of the study found that the degree of difficulties in learning mathematics for the fifth and sixth grades is high for some paragraphs and intermediate for other paragraphs, included the student’s field. The results also revealed that there were no statistically significant differences at the level of significance (α = 0.05) between the responses of the members of the study sample from male and female teachers to the degree of difficulties in learning mathematics for the fifth and sixth grades in all paragraphs, except in a paragraph "Curricula contain unimportant subjects." which showed statistically significant differences at the significance level (α = 0.05) where differences were found for female teachers. Moreover, the results revealed that there were no statistically significant differences at the level of significance (α = 0.05) between the responses of the members of the study sample of teachers to the degree of difficulties in learning mathematics for the fifth and sixth grades in all paragraphs due to the variable of the grade (fifth-sixth). The study also revealed a list of possible suggestions to address the difficulties encounter a student in mathematics.